Dancing girls, and other stories - Atwood, Margaret
Dancing Girls is Margaret Atwood’s highly praised first collection of short fiction. In it she explores the dark intricacies of the mind, the complexities of human relationships, and the clashes between cultures. In the stories, the mundane and the bizarre intersect in unexpected ways: ex-wives indulge in an odd feast at a psychiatrist’s funeral; a young student is pursued by an obsessed immigrant; an old woman stores up supplies against an impending cataclysm. The fourteen stories range in setting from Canada to England, from Mexico to the United States, and portray characters who touch us and arouse in us compassion and understanding. In this astonishing collection, Margaret Atwood maps human motivation we scarcely know we have. [By publisher]